Structural Transformation in Ethiopia: Evidence from Cereal Markets - Minten, Bart; Stifel, David; Tamru, Seneshaw (International Food Policy Research Institute, 2012)
We study cereal wholesale markets in Ethiopia in the last decade (2001–2011), a period that has been characterized by important local changes affecting agricultural markets, including strong economic growth, urbanization, improved road and communication infrastructure, an increase in importance of cooperatives and commercial farms, and a doubling in commercial surplus. We find that these changes are associated with significant declines in real price differences between supplying and receiving markets, in cereal milling margins, as well as in retail margins. Important improvements have thus happened in the last decade in Ethiopia’s food marketing system, traditionally identified as a major cause of food security problems in the country.